Determining spectral response of a photovoltaic device using polychromatic filters. Issue 5 (1st July 2014) - Sara, Ira Devi; Betts, Thomas R.; Gottschalg, Ralph
Abstract : This study introduces a new method for determining the spectral response of a photovoltaic (PV) device. Instead of illuminating the PV device under test with monochromatic beams at different wavelengths, the device is irradiated with different broadband spectra. Variations in the spectra are made by employing different types of polychromatic filters. The advantage of using these types of filters is the increase in the light intensity incident on the measurement plane, compared with narrowband filtered light. As a consequence, the spectral response measurement setup becomes very simple, comprising only a light source, a set of polychromatic filters, spectroradiometer and source‐meter unit. The spectral response is determined by fitting the short‐circuit currents measured under different spectra to a chosen spectral response model. The proposed method is verified by comparing the results to spectral response curves measured with a traditional monochromatic method, which show excellent agreement. From this analysis, it can be concluded that the proposed method is feasible as a new technique for determining the spectral response of a PV device.